Paradoxical Reasoning: An fMRI Study - Belekou, Antigoni; Papageorgiou, Charalabos; Karavasilis, Efstratios; Tsaltas, Eleftheria; Kelekis, Nikolaos; Klein, Christoph; Smyrnis, Nikolaos (Frontiers in Psychology, 2022)
Paradoxes are a special form of reasoning leading to absurd inferences in contrast to logical reasoning that is used to reach valid conclusions. A functional magnetic resonance imaging (fMRI) study was conducted to investigate the neural substrates of paradoxical and deductive reasoning. Twenty-four healthy participants were scanned using fMRI, while they engaged in reasoning tasks based on arguments, which were either Zeno’s like paradoxes (paradoxical reasoning) or valid/invalid statements (deductive reasoning). Clusters of significant activation for paradoxical reasoning were located in bilateral inferior frontal and middle temporal gyrus. Clusters of significant activation for deductive reasoning were located in bilateral superior and inferior parietal lobe, precuneus and inferior frontal gyrus. These results confirmed that different brain activation patterns are engaged for paradoxical versus deductive reasoning providing a basis for future studies on human physiological as well as pathological reasoning.